PHONOLOGICAL ANALYSIS OF SLANG USE IN SOCIAL MEDIA APPLICATION "X" - Tasya Febrianty; Ramadhani, Syafitri; Alya Rizky Ika Putri; Marshanda Amelya Octaviani; Endang Sholihatin (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
This article discusses the analysis of slang phonology in social media application "X", a social media application that is often used by some people to write and post tweets using slang varieties. This research aims (1) to find out the variety of slang used by the community in the "X" application; (2) to find out the phonological process of slang that occurs in the "X" application; (3) to find out the factors that influence the use of slang. This research uses descriptive qualitative method with data collection techniques using observation and screenshots. This research has the result that many people use slang in posts on the X application. Phonological changes in slang found in the form of removal of vowels and consonants and changes in the sound of a phoneme. There are 2 factors that make people use slang, namely internal factors and external factors.